EFEKTIVITAS PEMBELAJARAN MATEMATIKA MENGGUNAKAN PENDEKATAN OPEN-ENDED PADA MATERI LUAS SEGITIGA DAN SEGIEMPAT DI SMP - Agung Wahyu Aji; Halini Halini; Asep Nursangaji (Universitas Tanjungpura, 2021)
This research’s purposes were to know and describe the effectiveness of mathematicslearning uses an open-ended approach on the broad material of triangles andrectengles at SMPN 4 Tebas. There were three indicators that were used to determinedthe effectiveness of mathematics learning uses an open-ended approach, such: teacherimplementation in managing learning, learning activities of learners, and learningoutcome of learners. The method used was descriptive method. The form of researchused was experimental. There were two techniques to collecting data, that aremeasurement techniques and direct observation techniques. The research subject isclass VIIC at SMPN 4 Tebas. Based on the data analysis obtained, the result are: (1)teacher implementation in managing learning catagorized good with average score3,16; (2) learning activities of learners categorized active with average score 78,04%;(3) learning outcome of learners archieve classical completeness, namly as much as76,67% of learners archieving minimum learning completeness. Because threeindicators of effectiveness are fulfilled, it mean that the effectiveness of mathematicslearning uses an open-ended approach is effective to be applied to the broad materialof triangles and rectangles at SMPN 4 Tebas.Keyword: Broad Material Triangles and Rectangle, Effectiveness, Open-Ended Approach